"Through‐Space" Relativistic Effects on NMR Chemical Shifts of Pyridinium Halide Ionic Liquids. Issue 1 (27th November 2018) - Ariai, Jama; Saielli, Giacomo
Abstract: We have investigated, using two‐component relativistic density functional theory (DFT) at ZORA‐SO‐BP86 and ZORA‐SO‐PBE0 level, the occurrence of relativistic effects on the 1 H, 13 C, and 15 N NMR chemical shifts of 1‐methylpyridinium halides [MP][X] and 1‐butyl‐3‐methylpyridinium trihalides [BMP][X3 ] ionic liquids (ILs) (X=Cl, Br, I) as a result of a non‐covalent interaction with the heavy anions. Our results indicate a sizeable deshielding effect in ion pairs when the anion is I − and I3 − . A smaller, though nonzero, effect is observed also with bromine while chlorine based anions do not produce an appreciable relativistic shift. The chemical shift of the carbon atoms of the aromatic ring shows an inverse halogen dependence that has been rationalized based on the little C‐2s orbital contribution to the σ‐type interaction between the cation and anion. This is the first detailed account and systematic theoretical investigation of a relativistic heavy atom effect on the NMR chemical shifts of light atoms in the absence of covalent bonds. Our work paves the way and suggests the direction for an experimental investigation of such elusive signatures of ion pairing in ILs. Abstract : The effect of heavy atoms on the chemical shifts of light atoms in non‐covalent systems based on pyridinium halide ionic liquids is predicted by relativistic DFT calculations.